2022
DOI: 10.1002/hbm.26025
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal fusion analysis of functional, cerebrovascular and structural neuroimaging in healthy aging subjects

Xulin Liu,
Lorraine K. Tyler,
James B. Rowe
et al.

Abstract: Brain aging is a complex process that requires a multimodal approach. Neuroimaging can provide insights into brain morphology, functional organization, and vascular dynamics. However, most neuroimaging studies of aging have focused on each imaging modality separately, limiting the understanding of interrelations between processes identified by different modalities and their relevance to cognitive decline in aging. Here, we used a data-driven multimodal approach, linked independent component analysis (ICA), to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 129 publications
(245 reference statements)
3
4
0
Order By: Relevance
“…The decreases in CBF and default mode network activity are consistent with the commonly observed changes in perfusion [52, 53] and default mode network [54] in normal aging. We also demonstrated a significant decrease with age in global GMV, consistent with previous multimodal neuroimaging fusion studies [5557] and normal aging pattern of the brain [58]. More importantly, we illustrated the age- and cognition-relevant divergence of frontoparietal network integrity between pre-symptomatic genetic mutation carriers and non-carriers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The decreases in CBF and default mode network activity are consistent with the commonly observed changes in perfusion [52, 53] and default mode network [54] in normal aging. We also demonstrated a significant decrease with age in global GMV, consistent with previous multimodal neuroimaging fusion studies [5557] and normal aging pattern of the brain [58]. More importantly, we illustrated the age- and cognition-relevant divergence of frontoparietal network integrity between pre-symptomatic genetic mutation carriers and non-carriers.…”
Section: Discussionsupporting
confidence: 89%
“…The stability of the estimated ICs was evaluated across 100 ICASSO iterations [41]. Functional networks were identified from components by visualization and validated by spatially matching the components to pre-existing templates [42], in accordance with the previous methodology used to identify networks from ICs [43, 44]. The dorsal and ventral default mode network, the salience network, and the left and right frontoparietal network were selected, which are higher-order functional networks known to be associated with age- and FTD-related cognitive change [4547].…”
Section: Methodsmentioning
confidence: 99%
“…It is also plausible that the RSFA signal in ICA-identified regions captures multiple sources with different aetiology, particularly at boundaries of large vessels and adjacent perivascular space, that may exhibit different spontaneous brain activity at rest [67]. The latter illustrates the challenge of dissociating spatially overlapping sources of signal using univariate methods and motivate the use of data-driven and multimodal approaches [68], as underscored by our findings.…”
Section: Regional Distribution Of Cerebrovascular Reactivity Impairme...mentioning
confidence: 61%
“…This null result may be caused by small and unbalanced sub-groups per mutated gene but may also imply true commonalities in the vascular pathology downstream of the mutations’ molecular pathology. Previous neuroimaging studies have revealed gene mutation-specific brain changes in FTD [56, 69]. The CVR changes in frontal regions may reflect distinct mechanisms from the atrophy and perfusion alterations in temporal areas discovered in earlier FTD investigations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation